Analisis Tindak Tutur Ilokusi dalam Lirik Lagu Album Manusia Karya Tulus Sebagai Bahan Ajar Puisi di SMP - Tanti Aprilliani; Dewi Herlina Sugiarti; Sinta Rosalina (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the forms of classification of illocutionary speech acts in the song lyrics of the album Human by Muhammad Tulus Rusdi. Illocutionary speech acts have a communicative function in survival, between the interlocutor and the speech partner. In illocutionary speech acts there are many meanings contained in an utterance, so that with illocutionary speech acts, it can be seen the meaning and message contained in the lyrics of the Human album by Muhammad Tulus Rusdy. Tulus songs are famous for their very poetic lyrics and contain deep meaning. The source of the data in this study is the song lyrics in the Human Album by Muhammad Tulus Rusdy which consists of 10 songs, namely: Seventeen, Kelana, Remedial, Interaction, Ingkar, Falling Like, Nala, Be Careful on the Road, Self, and Satu. Time. Tulus released the Human album in early 2022, to be precise in March. This research is a theoretical research using a pragmatic approach. The method used in this research is descriptive qualitative. The data collection technique used in this study is an observation technique in the form of document analysis and recording. The results showed that there were 212 data included in the illocutionary speech act. Illocutionary speech acts include, 1) assertive, 2) directive, 3) commissive, 4) expressive and declarative.